The Influence of Workload and Work Stress on Employee Performance in Bekasi Regency - Cahyani, Dea (Talent: Journal of Economics and Business, 2024)
This study aims to analyze the effect of workload and work stress on employee performance in Bekasi Regency. Using a quantitative method with a probability sampling technique in the form of simple random sampling, this study collected data from 74 respondents through questionnaires distributed using g-form. Data analysis was carried out using the algorithm and bootstrapping methods with SmartPLS 3.0. The results showed that workload has a positive and significant effect on employee performance with a T-Statistic value of 2.211> 1.99 and a P-value of 0.027 <0.05. Work stress also showed a positive and significant effect on employee performance with a T-Statistic value of 4.121> 1.99 and a P-value of 0.000 <0.05. The R-square value of 0.323 indicates that workload and work stress have a 32% effect on employee performance, while the remaining 68% is influenced by other factors outside the research model. This study concluded that controlled workload and work stress can improve employee performance, but need to be maintained at ideal levels to maintain optimal productivity.